Virtual 3D tooth creation for personized haptic simulation training in access cavity preparation - Min-Hsun Hsu; Chia-Min Liu; Chun-Ju Chen; Hui-Wen Yang; Yu-Chao Chang (Elsevier, 2022)
Personalized medicine is a new medical concept to achieve patient-centered care. In dentistry, it is recognized for the customization of operative strategies and managements for oral diseases. Access cavity preparation in endodontic treatment is an irreversible procedure. Endodontic training will be more realistic by the implementation of clinical relevant 3D virtual reality technology. In this article, the authors first presented a personized case from a real patient to provide assess cavity preparation in haptic virtual reality dental simulator Simodont® (Nissin Dental Products Inc., Nieuw-Vennep, Netherlands). The practical framework to generate STL from cone beam computed tomography was demonstrated. A case of virtual tooth #26 access cavity preparation in Simodont® was established for trainee unlimited practices before performing the clinical procedure on a real patient. Taken together, access cavity preparation in a virtual environment using a 3D personized tooth may minimize procedural errors and facilitate clinical treatment outcome.